Hydrogen peroxide contributes to the ultraviolet‐B (280–315 nm) induced oxidative stress of plant leaves through multiple pathways. Issue 14 (17th May 2014) - Czégény, Gyula; Wu, Min; Dér, András; Eriksson, Leif A.; Strid, Åke; Hideg, Éva
Abstract : Solar UV‐B (280–315 nm) radiation is a developmental signal in plants but may also cause oxidative stress when combined with other environmental factors. Using computer modeling and in solution experiments we show that UV‐B is capable of photosensitizing hydroxyl radical production from hydrogen peroxide. We present evidence that the oxidative effect of UV‐B in leaves is at least twofold: (i) it increases cellular hydrogen peroxide concentrations, to a larger extent in pyridoxine antioxidant mutant pdx1.3‐1 Arabidopsis and; (ii) is capable of a partial photo‐conversion of both 'natural' and 'extra' hydrogen peroxide to hydroxyl radicals. As stress conditions other than UV can increase cellular hydrogen peroxide levels, synergistic deleterious effects of various stresses may be expected already under ambient solar UV‐B. Abstract : UV‐B can photosensitize hydroxyl radical production from metabolic H2 O2 . 308nm UV is more damaging to leaves which have less OH antioxidant pyridoxine. UV‐B may induce oxidative stress both directly and via OH from H2 O2 photolysis.